Evaluasi sifat fisika, kimia dan kandungan logam berat di dalam nata de coco yang dibuat menggunakan sumber nitrogen dari NPK - Budi Santosa; Wirawan Wirawan (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Nata de coco one of the beverage products produced from fermented coconut water using the help of starter Acetobacter xylinum. This product is very popular with people ranging from children to parents because the shape and texture resembles a gel. This study aims to evaluate the physical, chemical and heavy metal content in nata de coco made using nitrogen sources from NPK. The experimental plan used by The Complete Randomized Plan (RAL) is a single factor, the factor is the concentration of NPK consisting of 5 levels of K1 = 0.25%, K2 = 0.5%, K3 = 1%, K4 = 1.5%, K5 = 2%. Each treatment was repeated 5 times and the total sample observed a total of 25 pieces. The observed observation parameters of nata thickness, nata weight, total fiber content of nata and metal residue content in nata include Cu, Zn, Pb metals, all of which are observed at the end of fermentation (the 14th day of fermentation). The initial parameters of the formation of nata are observed from the beginning of fermentation until the nata sheet is first formed. The results showed that nata de coco made using nitrogen source from NPK concentration of 0.1% has the best physical and chemical properties namely thickness of nata: 1,438 cm, weight of nata: 309 grams, initial formation of nata 3.2 days and total fiber content of nata: 4.024%. The use of NPK produces residues in the form of heavy metals Cu and Zn while pb heavy metals are undetectable. The higher the concentration of NPK given as a source of nitrogen, the higher the residues of heavy metals Cu and Zn in the nata de coco.